If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6k + -1(8 + k) = -1(6k + 8) 6k + (8 * -1 + k * -1) = -1(6k + 8) 6k + (-8 + -1k) = -1(6k + 8) Reorder the terms: -8 + 6k + -1k = -1(6k + 8) Combine like terms: 6k + -1k = 5k -8 + 5k = -1(6k + 8) Reorder the terms: -8 + 5k = -1(8 + 6k) -8 + 5k = (8 * -1 + 6k * -1) -8 + 5k = (-8 + -6k) Add '8' to each side of the equation. -8 + 8 + 5k = -8 + 8 + -6k Combine like terms: -8 + 8 = 0 0 + 5k = -8 + 8 + -6k 5k = -8 + 8 + -6k Combine like terms: -8 + 8 = 0 5k = 0 + -6k 5k = -6k Solving 5k = -6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '6k' to each side of the equation. 5k + 6k = -6k + 6k Combine like terms: 5k + 6k = 11k 11k = -6k + 6k Combine like terms: -6k + 6k = 0 11k = 0 Divide each side by '11'. k = 0 Simplifying k = 0
| 8+6(9-5)(9-5)= | | 5x-34=9 | | x/4+100=150 | | 24.36/12=x/8 | | X+24=9x | | 5+b=-15-3 | | 2[x-[x-(x-1)]]+(x+2)=256 | | -13+5(1+4m | | -13+5(1+4m | | -5(4n-7)=60 | | 3(v-2)=5v+7-2(-8v-1) | | 10m-10-5m=60 | | 4x^3-35x^2+36x-9=0 | | 3(50-x)+7x=5(50) | | 2/3-1/6q=5/6q+1/3 | | 3[3x-4(y-3)]= | | 146+2x= | | 6p-12+3p=12(4) | | (5/8)w=40 | | (r/7)(7/r)=0 | | -3x=2x+25 | | 5y+z=t | | 3x-11=9x+7 | | 5z+4=3 | | 10r^2-81r+8=0 | | x+3=2+-4 | | 1/100(j-200)=4.5 | | 6(x-4)=66 | | -1+6=y-5 | | 2.4=2(x+4) | | X+5=-10+6-2x-3 | | -3/2x-5/4y=15 |